The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9tc02188d
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermoelectric performance of bilayer Bi2O2Se by the band convergence approach

Abstract: The first-principles calculations show that band convergence can be achieved by decreasing the interlayer distance of bilayer Bi2O2Se, which is beneficial to improve its thermoelectric performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 66 publications
7
39
0
1
Order By: Relevance
“…where h, k B , m*, C, and E 1 are the Planck constant, Boltzmann constant, effective mass, elastic constant, and DP constant, respectively. For the electronic thermal conductivity κ e , in this study, it is obtained using the Wiedemann-Franz law, that is, κ e LσT (Jonson and Mahan, 1980) Besides, κ e can also be obtained directly from the BoltzTraP2 code, that is, κ e κ 0 − TσS 2 (Madsen et al, 2018) A recent study put forward that the results which were obtained from the output of BoltzTraP and from using the Wiedemann-Franz law agree very well with each other (Li M. et al, 2019).…”
Section: Computational Detailsmentioning
confidence: 56%
See 1 more Smart Citation
“…where h, k B , m*, C, and E 1 are the Planck constant, Boltzmann constant, effective mass, elastic constant, and DP constant, respectively. For the electronic thermal conductivity κ e , in this study, it is obtained using the Wiedemann-Franz law, that is, κ e LσT (Jonson and Mahan, 1980) Besides, κ e can also be obtained directly from the BoltzTraP2 code, that is, κ e κ 0 − TσS 2 (Madsen et al, 2018) A recent study put forward that the results which were obtained from the output of BoltzTraP and from using the Wiedemann-Franz law agree very well with each other (Li M. et al, 2019).…”
Section: Computational Detailsmentioning
confidence: 56%
“…Therefore, some methods like doping (Liu et al, 2008), alloying (Row et al, 1981), and nanostructuring (Yuan et al, 2018) were reported to enhance the ZT value. Except for these approaches, screening new TE materials is also an effective strategy to improve the ZT value via experimental research (Nielsen et al, 2013;Tang et al, 2015;Li et al, 2018) and theoretical predictions [such as first-principles calculations (Wang et al, 2017;Ouyang et al, 2018) and high-throughput computations (Chen et al, 2016;Li M. et al, 2019;Li R. et al, 2019;Ortiz et al, 2019)].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum PF value (∼5.745 m W mK −2 at 300 K) of pentagonal NiTe 2 monolayer is considerably higher than that of the thermoelectric material SnSe (∼0.250 m W mK −2 at 300 K) with the cubic ( Fm 3̄ m ) phase at room temperature. 79 Similar to the bilayer Bi 2 O 2 Se (∼9.000 m W mK −2 at 300 K), 80 the pentagonal NiTe 2 monolayer could be a promising thermoelectric material with high performance.…”
Section: Resultsmentioning
confidence: 99%
“…zT of 0.3 at 3000 K was obtained in rGO experimentally and Seebeck coefficient can be improved by N or B doping 222‐224 . Other oxides, such as Bi 2 O 2 Se nanosheet, 2D Bi 2 O 2 S thin film and phosphorene oxide, have excellent predicted thermoelectric performance but little experimental work has been carried out so far 29,225‐229 . Stacking 2D layers or forming heterostructures is another way to enhance properties by combining the advantages of components; however, the present studies are mainly in theoretical research, such as graphene/black phosphorous/graphene, BiSb/AlN, graphene/Sb 2 Te 3 and Bi‐Sb/Co 203,230‐232 with the predicted values of zT around 2–3.…”
Section: Thermoelectric Performance Of Iva and Va Xenesmentioning
confidence: 95%